A distance between populations for one-point crossover in genetic algorithms - Manzoni, Luca (2021)
Manzoni, L., Vanneschi, L., & Mauri, G. (2012). A distance between populations for one-point crossover in genetic algorithms. Theoretical Computer Science, 429, 213-221. https://doi.org/10.1016/j.tcs.2011.12.041